ETIKA SEORANG GURU DALAM PROSES BELAJAR MENGAJAR - Azhara, Sabrina; Ginting, Rahmadani Fitri (Sindoro: Cendikia Pendidikan, 2024)
The ethics of a teacher in the teaching and learning process plays a crucial role in creating a positive and productive educational environment. Teachers are figures who hold a respectable and noble position, as expressed by al-Ghazali: "The most glorious creature in the kingdom of heaven is a man who knows, practices, and teaches." Thus, teachers are believed to occupy key positions in education, serving as sources of inspiration and enlightenment for students. As educators, teachers have a significant impact on the character and knowledge development of their students. Therefore, a teacher must be a role model to be emulated, both in knowledge and behavior. The ideal teacher should possess various qualifications related to physical, ethical, moral, and scientific aspects. In the context of ethics, there are three interrelated distinctions: a general pattern or way of life, a set of rules or "moral code," and an investigation into the way of life and rules of behavior. Through understanding and applying good ethics, teachers can create a learning atmosphere that not only educates academically but also shapes students' character, making them quality individuals with integrity. Etika seorang guru dalam proses belajar mengajar memegang peranan penting dalam menciptakan lingkungan pendidikan yang positif dan produktif. Guru adalah sosok yang memiliki posisi terhormat dan mulia, seperti yang diungkapkan oleh al-Ghazali, “makhluk paling mulia di kerajaan langit adalah orang yang berilmu, mengamalkan, dan mengajarkan.” Dengan demikian, guru diyakini menempati posisi kunci dalam pendidikan, berfungsi sebagai sumber inspirasi dan pencerahan bagi siswa. Sebagai pendidik, guru memiliki dampak signifikan terhadap perkembangan karakter dan pengetahuan siswa. Oleh karena itu, guru harus menjadi teladan yang dapat diikuti, baik dalam pengetahuan maupun perilaku. Guru ideal seharusnya memiliki berbagai kualifikasi yang terkait dengan aspek fisik, etika, moral, dan ilmiah. Dalam konteks etika, terdapat tiga perbedaan yang saling terkait: pola atau cara hidup yang umum, seperangkat aturan atau "kode moral," serta kajian tentang cara hidup dan aturan perilaku. Melalui pemahaman dan penerapan etika yang baik, guru dapat menciptakan suasana belajar yang tidak hanya mendidik secara akademis tetapi juga membentuk karakter siswa, menjadikannya individu yang berkualitas dan berintegritas.